The Influence of Transformational Leadership and Work Conflict on Employee Performance and Change Management in Hospitality Companies - Elsa Mariska Andini; Elistia Elistia (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The hospitality industry in Indonesia faces intense competition and rapid changes in business environments, requiring effective leadership to sustain employee performance and support successful change management. The suboptimal implementation of transformational leadership and the presence of work conflict have the potential to decrease productivity and hinder organizational adaptability. This study aims to analyze the influence of transformational leadership and work conflict on employee performance and change management, as well as examine the moderating role of transformational leadership in the relationship between work conflict and employee performance. This research employed a quantitative approach using a survey method by distributing questionnaires to 160 employees of Ascott Group Jakarta. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings indicate that transformational leadership has a significant positive effect on employee performance and change management, while work conflict negatively influences employee performance. Moreover, transformational leadership can weaken the negative impact of work conflict on employee performance. This study provides practical implications for hotel management in optimizing transformational leadership to enhance performance, manage conflict, and support successful organizational change.